Electrocatalytic regeneration of atmospherically aged MoS2 nanostructures via solution-phase sulfidation. Issue 32 (11th March 2016) - Burch, H. A.; Isaacs, M.; Wilson, K.; Palmer, R. E.; Rees, N. V.
Abstract : The loss in performance of MoS2 as a catalyst due to exposure to air can be reversed by electrochemical reduction of thiosulfate. Abstract : The performance of MoS2 as a hydrogen evolution catalyst is diminished by exposure to air. We demonstrate a solution phase technique to resulfidate MoS x O2− x using Na2 S2 O3 . The success of the method was judged by performance as a H + reduction catalyst. Following sulfidation samples displayed a favourable decrease in both onset potential and Tafel slope, with the best decreasing from −0.23 V to −0.18 V ( vs. SHE), and 282 mV dec −1 to 87 mV dec −1 respectively. Ageing studies indicate that this method may be used to recycle the MoS2 repeatedly without losing catalytic performance, although repeated sulfidation did result in homogenisation of the nanostructure.